"Shoulder Anterior Capsular Block: An Effective Strategy for Alleviating Pain During Shoulder Mobilisation in Adhesive Capsulitis Patients": A Case Series - Bhavani Vaidiyanathan; Saravanakumar Sundaresan; I.Joseph Raajesh (Archives of Anesthesia and Critical Care)
Frozen shoulder is a condition of varying severity characterized by the gradual development of global limitation of active and passive shoulder motion where radiographic findings are limited and associated with severe shoulder pain. Frozen shoulder is also referred to as adhesive capsulitis, painful stiff shoulder, and periarthritis. Treatment typically focuses on reducing shoulder pain and restoring joint mobilisation. In the context of shoulder mobilization, the predominant nerve blocks encompass the interscalene, supraclavicular upper trunk block collectively referred to as the SCUT block, as well as the axillary nerve block. These nerve blocks demonstrate high efficacy in delivering targeted analgesia. However, a notable limitation of these interventions is the concomitant motor blockade and phrenic nerve block induced by them. This motor blockade poses a significant impediment to the initiation of early rehabilitation, thereby delaying the commencement of rehabilitative exercises and intervention. Shoulder Anterior Capsular Block is a motor sparing block which can be effectively used in shoulder mobilisation.